Application of Accounting Information System In Improving the Efficiency and Effectiveness of Financial Management at Coffee Shop Coffee Time - Maulia, Suci (Journal of Community Research and Service, 2024)
This research aims to analyze how the application of SIA improves the efficiency and effectiveness of financial management that occurs at the Kopi Time coffee shop. Researchers use case study research to examine how to investigate object design. The research subject in this study is the sales accounting information system for the KopiTime (Kowa) coffee shop. The data collection techniques required in this research are observation, interviews, documentation and library research. Data analysis techniques are carried out by collecting data, classifying data material, editing and presenting data. Researchers found that computer systems can store information more effectively, efficiently and accurately for use by coffee shop owners in making financial reports, managing human resources and determining product HPP in accordance with research findings. This is the key to facing competition and supporting business growth in the digital era. This activity provides important insight into the importance of accounting information systems for MSMEs in managing their finances and maintaining business sustainability amidst growing economic challenges.